Perkembangan Penelitian Tumbuhan Ciplukan (Physalis Angulata) Dalam 10 Tahun Terakhir: Kajian Bibliometrik - Nurfirianto, Akbar; Listiawati, Emi; Nabila, Putri; Suhartono, Eko; Komari, Noer (Symbiotic: Journal of Biological Education and Science, 2025)
Research on the ciplukan plant (Physalis angulata) has rapidly advanced in the field of health. This article examines the development of research on Physalis angulata over the past decade, utilizing data from scientific journal publications spanning from 2014 to 2023. This bibliometric analysis maps and analyzes the evolution of research concerning Physalis angulata by employing the Open Knowledge Map web server and the VOSViewer application. The methods include the collection of relevant scientific literature, followed by visual analysis to identify research trends, collaboration networks, and dominant research topics. The mapping results indicate that research on this plant increasingly focuses on its pharmacological potential and applications in biotechnology, with significant growth in cross-country scientific collaboration. This study provides in-depth insights into the direction of Physalis angulata research and offers recommendations for further studies, particularly in practical applications that could enhance economic value and public health. These findings are expected to serve as a guide for researchers and practitioners in developing the utilization of Physalis angulata more effectively.